86.9k views
3 votes
What is the expression and value of “six less than nine times the sum of a number and eight” when n = 5

A.9(n+8)-6, when n=5, the value is 111
B. 6-9(n+8), when n = 5, the value is 111
C. 9(n)+8-6, when n = 5 the value is 47
D.6-9(n), when n = 5, the value is 47

2 Answers

1 vote

Answer:

The expression is 9(n + 8) - 6, the value is 111 ⇒ answer A

Explanation:

* Lets explain how to solve the problem

- We have a statement:

" six less than nine times the sum of a number and eight"

- When we solve we will start by the last part

- The last part is the sum of a number and 8

- Assume that the number is n

∵ The sum is the answer of adding

∴ The sum of a number and eight is ⇒ n + 8

- Nine times the sum

∵ The sum is n + 8

∵ Nine times means multiply the sum by 9

∴ Nine times the sum is ⇒ 9(n + 8)

- Six less than nine times the sum

∵ Nine times the sum is 9(n + 8)

∵ Six less than means subtract 6 from nine times the sum

∴ Six less than nine times the sum is ⇒ 9(n + 9) - 6

* The expression is 9(n + 8) - 6

- Lets evaluate the expression when n = 5

∵ 9(n + 8) - 6

∵ n = 5

∴ The value = 9(5 + 8) - 6

∴ The value = 9(13) - 6

∴ The value = 117 - 6

∴ The value = 111

* When n = 5 the value of the expression is 111

User Colateral
by
5.8k points
4 votes

Answer:

The expression is 9(n + 8) - 6, the value is 111 ⇒ answer A

Explanation:

* Lets explain how to solve the problem

- We have a statement:

" six less than nine times the sum of a number and eight"

- When we solve we will start by the last part

- The last part is the sum of a number and 8

- Assume that the number is n

∵ The sum is the answer of adding

∴ The sum of a number and eight is ⇒ n + 8

- Nine times the sum

∵ The sum is n + 8

∵ Nine times means multiply the sum by 9

∴ Nine times the sum is ⇒ 9(n + 8)

- Six less than nine times the sum

∵ Nine times the sum is 9(n + 8)

∵ Six less than means subtract 6 from nine times the sum

∴ Six less than nine times the sum is ⇒ 9(n + 9) - 6

* The expression is 9(n + 8) - 6

- Lets evaluate the expression when n = 5

∵ 9(n + 8) - 6

∵ n = 5

∴ The value = 9(5 + 8) - 6

∴ The value = 9(13) - 6

∴ The value = 117 - 6

∴ The value = 111

* When n = 5 the value of the expression is 111

User Akhilesh Sinha
by
5.9k points